Staging the end of the world theatre in a time of climate crisis - Kulick, Brian (Methuen Drama, 2023)
"This book is a brief history of the end of the world as seen through the eyes of theatre. It examines a wide range of plays, from Euripides and Bhasa, to medieval mystery cycles, through Shakespeare, Pushkin, Ibsen, Chekhov, Brecht, and Samuel Beckett, to Caryl Churchill's Far Away, Tony Kushner's Slavs!, and Anne Washburn's Mr. Burns, A Post-Electric Play. Through analyzing these alongside contemporary thinkers, this study helps guide and galvanize the reader in grappling with the climate crisis"-- Back cover.